Lise Öğretmenlerine Verilen Temel İlkyardım Eğitiminin Etkililiğinin Değerlendirilmesi - Özyürek, Pakize; Bayram, Fatma; Beştepe, Gülbahar; Ceylantekin, Yeşim; Ciğerci, Yeliz; Çelik, Yasemin; Kuyucuoğlu, Nazmiye; Karaca, Şemsettin; Temel, Safiye; Yılmazer, Asuman (Afyon Kocatepe Üniversitesi, 2013)
This study was aimed to evaluate the efficiency of two days training given to the high school teachers working in Afyon city center. This study was performed in cluster sample method selected five high schools located in Afyonkarahisar city center between 01 September 2008-01 September 2009. N=195 teachers created the study sample . Data have been evaluated with t-test, ANOVA analysis in independent groups. The average of point FAK of among teachers of post test ( 80.52 ± 11.25) were considerably higher than that of pre test (48.51 ±14.18), (p<0.05). The questions of the subjects which were given the more correct answers were, respectively, approach to burned, sprains of and fracture of. Most common situations which require first aid are told to be, respectively, Fainting, hemorrhage and minimal injury by teachers. First aid knowledge among teachers were considered to be insufficient. Lectures on first aid must be included in curricumulus of training and education instutions of various levels.
The Efficiency Evaluation of the Training Basic First Aid Given to High School Teachers
Keywords: İlkyardım; Temel Yaşam Desteği; Eğitim